1972
DOI: 10.1099/00221287-72-2-243
|View full text |Cite
|
Sign up to set email alerts
|

Wall Replication in Saccharomyces Species: Use of Fluorescein-conjugated Concanavalin A to Reveal the Site of Mannan Insertion

Abstract: S U M M A R YThe wall mannan in dividing Saccharomyces cells was labelled by exposing the yeasts to fluorescein-conjugated concanavalin A. The yeasts were then allowed to grow in the absence of excess staining reagent and were examined by fluorescence microscopy at several intervals after the re-initiation of growth. The newly synthesized mannan was non-fluorescent and, thus, could be easily distinguished from the material present at the outset. Most new mannan was deposited in the wall surrounding the bud, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 5 publications
(8 reference statements)
7
71
0
Order By: Relevance
“…In agreement with Tkacz et al (1971), we have also shown that wall mannan components are the receptors for Con A binding and the subsequent agglutination. In animal cells, there is a substantial body of evidence that a 'clustering' of Con A receptors is one of the prerequisites for cells to agglutinate (Nicolson, 1974).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In agreement with Tkacz et al (1971), we have also shown that wall mannan components are the receptors for Con A binding and the subsequent agglutination. In animal cells, there is a substantial body of evidence that a 'clustering' of Con A receptors is one of the prerequisites for cells to agglutinate (Nicolson, 1974).…”
Section: Discussionsupporting
confidence: 70%
“…In keeping with these considerations, and in accord with the fluorescein-conjugated Con A binding studies of Tkacz et al (1971), we found that another strain of C. albicans ( A ,~) and also Saccharomyces cerevisiae, known to have a-mannan exposed on its surface (Bacon et al, 1969;Phaff, 1971), were agglutinated by Con A whereas a Rhodotorula glutinis strain, known not to contain a-mannan, was not agglutinated.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Budding can therefore be seen as a process of polarized secretion. Studies on the incorporation of cell wall components such as cell wall-bound acid phosphatase , mannan (Farkas et al, 1974), and glucan (Tkacz and Lampen, 1972) have shown that during most of the budding process, secretion is directed to the tip of the growing bud. When the daughter cell is about two-thirds the size of the mother cell, secretion becomes isotropic over the en-* Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…The report of lecin interaction to fungal, such as fluorescein-conjugated wheat germ agglutinin has been shown to be an effective probe to detect chitin on hypha surfaces. (Barkai and Sharon, 1978;Galun et al, 1976;Galun et al, 1981;Mirelman et al, 1975;Molano et al, 1980;Tkacz and Lampson, 1972;Tracz et al, 1971;Tropchin et al, 1981). In 1975 Mirelman et al was found wheat germ agglutinin (WGA) can be inhibits spore germination and hyphal growth of Trichoderma viride and interferes with the synthesis of chitin (Mirelman et al, 1975).…”
Section: Application To Antimicrobial Activitymentioning
confidence: 99%